Uporaba programa upravljanja območij Natura 2000 v presoji sprejemljivosti - Klemenčič, Tina (Varstvo narave, 2016)
In April 2015, the Slovenian Government adopted the Natura 2000 Management Programme for Slovenia for the period of 2015-2020. It has been prepared as a result of cooperation between the Ministry for the Environment and Spatial Planning, the Institute of the Republic of Slovenia for Nature Conservation, numerous experts on species and natural habitats and other stakeholders. The programme contains detailed conservation objectives and measures for each qualifying species or natural habitat in every Natura 2000 site in Slovenia. The aim of the article is to present how Natura 2000 Management Programme is used within appropriate assessment. Since the appropriate assessment, as set down in Article 6.3 of Directive on the conservation of natural habitats and of wild fauna and flora, aims to assess the impact of a plan or project on the conservation objectives of the site, the Natura 2000 Management Programme has become an important piece of groundwork for the assessment.
Keywords: appropriative assessment; conservation objectives; management; Natura 2000; presoja spremenljivosti; program upravljanja; programme; upravljanje območij; varstveni cilji